Pengaruh Desain Kerja dan Manajemen Teknologi Informasi Terhadap Mutu Pelayanan Guru SMK - Toto Widiarto (Peneliti.net, 2019)
Management of information technology and design work is very close to the services that will be provided to students. Establishing a good work design is a good part of planning. Information management can be applied in the era of digital technology. The purpose of this study is to determine whether Design Work influences the Quality of Teacher Services through Information Technology Management and Educational Communication. This research was conducted at State Vocational School 36 Samata, Gowa, South Sulawesi. By distributing questionnaires to 100 respondents with Path Analysis. The results of this study indicate that Design Work has an effect on the Quality of Teacher Services at SMK Samata, Gowa, South Sulawesi, through Information and Communication Technology Management.